KOMUNIKASI RELIGIUS (STUDI FENOMENOLOGI TENTANG KOMUNIKASI RELIGIUS KONVERSI AGAMA KRISTEN KE AGAMA ISLAM DI GARUT KOTA) - Adnan, Iis Zilfah; Nurhadi, Zikri Fachrul; Kurniawan, Achmad Wildan; Kurniawan, Kurniawan (UIN Antasari Banjarmasin, 2017)
This study aims to discover and explain the motives, experiences and meaning of conversion of religion from Christian Religion to Islam. The theory used is the theory of phenomenology that explains the structure of the conscious experience, as well as studying the form of experience from the point of view of the person who experienced it directly who has the openness and availability to be explored. This research method using qualitative approach through participant observation, depth interview, and literature study. The subject of research is the perpetrator who convert Christianity to Islam as the main informant who represented by purposive sampling technique which amounted to 7 people in Garut City. The result of the research shows that it produces several categorizations related to the motive of purpose (future), that is to get the happiness of the world and the hereafter, enlightenment, life balance, get ridho, magfiroh, togetherness and blessing, and motif because (past) marriage, perfect religion, acceptable common sense and one aqidah in couples. While the perpetrator's experience of happiness is born inward, gaining knowledge of the new teachings of religion, life becomes more valuable and affectionate. While the meaning contained for the actors is the change of life procedures, the procedures of worship, the movement of beliefs and guidelines in life.